2023
DOI: 10.1111/1756-185x.14923
|View full text |Cite
|
Sign up to set email alerts
|

Social cognitive theory to improve symptom appraisal and help‐seeking among patients with autoimmune rheumatic diseases: A qualitative study

Ling Xiang,
Sungwon Yoon,
Andrea H. L. Low
et al.

Abstract: AimSocial cognitive theory (SCT) has been successfully employed to improve symptom appraisal and help‐seeking among patients with various conditions but is yet to be applied in the context of autoimmune rheumatic diseases (ARDs). This study aimed to explore the applicability of SCT in and possible approaches to improving symptom appraisal and help‐seeking of patients with ARDs, one of the key barriers to earlier diagnosis.MethodsSemi‐structured interviews were conducted with 33 ARD patients with a prolonged pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Second, some of the concepts of SCT (behavioural competence, self‐efficacy, observational learning, reinforcement, etc.) have been successfully used to improve help‐seeking behaviours in patients with different health conditions (Islam et al., 2023 ), including application to symptom assessment and illness perception (Xiang et al., 2023 ). According to the research conducted by Cornally and McCarthy ( 2011 ), it indicated that the complex decision‐making process begins with the recognition and definition of a problem, which leads to the decision to act, and this is influenced principally by social‐cognitive factors.…”
Section: Introductionmentioning
confidence: 99%
“…Second, some of the concepts of SCT (behavioural competence, self‐efficacy, observational learning, reinforcement, etc.) have been successfully used to improve help‐seeking behaviours in patients with different health conditions (Islam et al., 2023 ), including application to symptom assessment and illness perception (Xiang et al., 2023 ). According to the research conducted by Cornally and McCarthy ( 2011 ), it indicated that the complex decision‐making process begins with the recognition and definition of a problem, which leads to the decision to act, and this is influenced principally by social‐cognitive factors.…”
Section: Introductionmentioning
confidence: 99%